Cost-effectiveness of ranibizumab and aflibercept to treat diabetic macular edema from a US perspective: analysis of 2-year Protocol T data. (3rd March 2020) - Holekamp, Nancy; Duff, Steven B.; Rajput, Yamina; Garmo, Vincent
Abstract: Aims: Protocol T (NCT01627249) was a head-to-head study conducted by the Diabetic Retinopathy Clinical Research Network that compared intravitreal aflibercept, bevacizumab, and ranibizumab for the treatment of diabetic macular edema (DME). A cost-effectiveness analysis accompanying the 1-year data of Protocol T revealed that aflibercept was not cost-effective vs ranibizumab for all patients, but could have been cost-effective in certain patient sub-groups if the 1-year results were extrapolated out to 10 years. The present study evaluated the cost-effectiveness of US Food and Drug Administration-approved anti-vascular endothelial growth factor agents (ranibizumab, aflibercept) for treatment of DME using the 2-year data from Protocol T. Methods: Costs of aflibercept 2.0 mg or ranibizumab 0.3 mg, visual acuity (VA)-related medical costs, and quality-adjusted life-years (QALYs) were simulated for eight VA health states. Treatment, adverse event management, and VA-related healthcare resource costs (2016 US dollars) were based on Medicare reimbursement and published literature. VA-related health utilities were determined using a published algorithm. Patients were stratified by baseline VA: 20/40 or better; 20/50 or worse. Results: Total 2-year costs were higher, and QALYs similar, for aflibercept vs ranibizumab in the full cohort ($44, 423 vs $34, 529; 1.476 vs 1.466), 20/40 or better VA sub-group ($40, 854 vs $31, 897; 1.517 vs 1.519), and 20/50 or worse VA sub-group ($48, 214 vs $37, 246; 1.433 vs 1.412), respectively. Incremental cost-effectiveness ratios in the full cohort and 20/50 or worse VA sub-group were $986, 159/QALY and $523, 377/QALY, respectively. These decreased to $711, 301 and $246, 978 when analyses were extrapolated to 10 years. Limitations: Key potential limitations include the fact that VA was the only QALY parameter analyzed and the uncertainty surrounding the role of better- and worse-seeing eye VA in overall functional impairment. Conclusions: This analysis suggests that aflibercept is not cost-effective vs ranibizumab for patients with DME, regardless of baseline vision.